2019
DOI: 10.1108/mhsi-08-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Recovery colleges and dementia courses – a scoping survey

Abstract: Purpose The purpose of this paper is to understand how dementia is represented within current UK Recovery College courses and how people with dementia are involved with such courses. Design/methodology/approach A scoping survey was developed with seven multiple choice questions. Information was collected to find out: How many Colleges are currently offering dementia courses; have previously offered courses or plan to start offering courses; how they have developed their courses; who delivers them; who can at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This may create more positive social-psychological environments ( 3 ). A UK scoping survey found that mental health organisations are incorporating dementia into Recovery College programmes ( 16 ). However, evidence from experiences of co-production with people with dementia in such programmes is scarce; only two published reports were found.…”
Section: Introductionmentioning
confidence: 99%
“…This may create more positive social-psychological environments ( 3 ). A UK scoping survey found that mental health organisations are incorporating dementia into Recovery College programmes ( 16 ). However, evidence from experiences of co-production with people with dementia in such programmes is scarce; only two published reports were found.…”
Section: Introductionmentioning
confidence: 99%
“…We found diversity among service user students, although some groups were underrepresented. Recovery Colleges are adapting to encourage engagement of these students, for example, coproducing more dementia courses (Lowen et al, 2019). A new form of Recovery College, "Discovery Colleges," are being developed for younger students (Hopkins et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At the service delivery level, the GO programme can be commissioned locally and delivered by anybody who works with people living with dementia who adheres to the values and principles of the programme. A range of organisations are developing and delivering courses for people living with dementia, for example Recovery Colleges ( Lowen et al, 2019 ) and our partner organisation Innovations in Dementia. The GO programme is continuing to be implemented through AgeUK.…”
Section: Discussionmentioning
confidence: 99%